Export of N, P and K in barley subjected to fertilizer doses formulated with and without humic substance at sowing (Acta Scientiarum. Agronomy, 2019)
The aim of this study was to evaluate the effect of nitrogen fertilization with and without humic acid in barley cultivars on the export of nitrogen, phosphorus and potassium grains. The experiment was performed in the city of Guarapuava, PR, during the 2015 and 2016 growing seasons. The experimental design was in RCB in factorial 5 x 2, with the following sowing fertilization (kg ha-1): 0, 100 NPK, 100 NPK+HS, 250 NPK, 250 NPK+HS and two cultivars, BRS Brau and BRS Elis. The dose of 250 kg NPK with humic substance increased the nitrogen export to barley grains, with the highest levels occurring in the BRS Brau cultivar under favorable climatic conditions. Under favorable climatic conditions, the export of phosphorus to barley grains in the agricultural crop was not influenced by the humic substance, with the highest levels occurring in the BRS Brau cultivar. The dose of 100 kg NPK with humic substance increased the export of potassium to barley grains, with the highest levels occurring in the BRS Brau cultivar regardless of climatic condition. There were correlations between nitrogen and phosphorus levels in grains and between phosphorus content and grain yield.